DEVELOPMENT OF AN E-WORKSHEET SUPPORTED BY LIVEWORKSHEET AND WORDWALL TO IMPROVE ELEMENTARY STUDENTS’ COGNITIVE COMPETENCE ON THE TOPIC OF NATURAL FEATURES - Dina Suci Ramadhani; Dhiniaty Gularso (Universitas Negeri Surabaya, 2025)
This study aims to determine the feasibility, practicality and effectiveness of E-LKPD assisted by Liveworksheet and Wordwall to improve the cognitive competence of elementary school students in the material of natural features. Research and development of the ADDIE model developed by Robbert Mariabe Branch is the type of research used in this study. The model consists of five steps, namely Analyze, Design, Development, Implementation, Evaluation. This study was implemented on 26 fourth-grade students of SD Masjid Syuhada Yogyakarta. Research data were collected through observation, interviews, questionnaires and tests. Meanwhile, data analysis used the paired sample t-test. Based on the study, it shows that E-LKPD assisted by Liveworksheet and Wordwall is very feasible to use. This assessment refers to the results of the assessment of the media expert validator with a percentage of 85.33% and the validation of the material expert which reached 99.13%. In addition, the results of student responses showed a percentage of 77% categorized as practical, while the teacher's response reached 95% categorized as very practical. E-LKPD assisted by Liveworksheet and Wordwall was also declared effective in terms of the average pretest score of 57.40 increasing to 78.07 in the posttest after using E-LKPD. This increase was proven significant based on the results of the paired sample t test which produced a significance value (Sig. 2 tailed) of 0.000 (<0.05).